Gender analysis of climate stressed rice-based systems in Mali - Diabate, Fatoumata; Mujawamariya, Gaudiose (Africa Rice Center, 2023)
Agriculture and livestock represent the main incomegenerating activity for women and youth in the rural areas of Mali. It is expected that climate change will lead to a reduction in food production due to changes in rainfall patterns and temperature in Africa (Awojobi and Tetteh, 2017), and Mali is facing the same challenges. To cope with such climateinduced stress, women and youth need information and access to climate-smart technologies. This study analyzes the role of women in rice-based systems heavily affected by climate stress, and their access to resources on climate-smart agriculture (CSA) and Climate Information Services (CIS) in Mali. Mixed methods were applied: a quantitative study covered 766 male and female respondents in 383 households and a qualitative investigation engaged 134 women and 155 men in 34 focus group, plus 29 key informants in the major rice-growing regions in Mali. The study showed large gaps between female and male farmers’ access to resources: specific gender constraints in the rice-based activity include access to land, improved seeds, rice farming, machinery, formal credit facilities, extension services, labor force, fertilizers and climate information. Particularly, the willingness to maintain women in the conditions of dependency was observed, hence, they were likely to abandon rice production or remain in labor-wage activities due to multiple climaterelated challenges they were facing